The Results of a One-Time Crystallized Phenol Application for Pilonidal Sinus Disease - Girgin, Mustafa; Kanat, Burhan Hakan (Springer India, 2014)
The aim of this study was to investigate the cure rate after a one-time phenol application for pilonidal sinus disease. Forty-eight patients diagnosed with pilonidal sinus from May 2006 to September 2009 were retrospectively reviewed. They were all managed under the same polyclinic conditions in different hospitals by the same surgeon under local anesthesia. Crystallized phenol was applied a total of 97 times on 48 patients. The median follow-up was 22 months (range, six to 38 months). Two patients (4 %) could not participate in the follow-up. One of these patients had 12 sinuses and didn't continue treatment after eight applications of phenol, and the other had nine sinuses and didn't continue treatment after five applications of phenol. The one-time application cure rate was 64.5 %, and the rate of success was 95 % with two or more applications. Recurrence did not occur during this period. A one-time phenol application is an effective treatment for pilonidal sinus disease. Hence, it can be an alternative to surgical treatment.
Keywords: Pilonidal disease; Crystallized Phenol; Treatment; Outpatient surgery